PEMBINAAN UMKM BERBASIS KEMITRAAN: SOLUSI UNTUK MENINGKATKAN DAYA SAING DAN PRODUKTIVITAS - Nur Endah Retno Wuryandari; Sri Anjarwati; Setiyo Purwanto; Margono Sugeng; Didin Hikmah Perkasa; Melly Melly (LP2M STP Mataram, 2023)
Development of Micro, Small, and Medium Enterprises (MSMEs) in Situgadung Village, Tangerang, by Universitas Dian Nusantara (UNDIRA) through a partnership with IKRT Family Care Plus emerges as a solution to address challenges faced by MSMEs, particularly in management, technological adaptation, and product certification. The program provides technological support for MSMEs, including initiatives for financial reporting, SOP development, online marketing, and strengthening human resource competencies. UNDIRA's involvement in financial reporting, production tool design, and process automation is expected to have a positive impact on the growth of IKRT Family Care Plus, generating employment opportunities, and enhancing the quality of environmentally friendly products. This program can also serve as a partnership model for other educational institutions, reinforcing MSMEs, and supporting environmental sustainability